Never send a human to do a machine's job correcting the top 5 EdTech mistakes - Zhao, Yong 1965-; Zhang, Gaoming; Lei, Jing; Qiu, Wei (Corwin, 2016)
Do what you do best and let technology do the rest Technology has transformed our lives. Virtually every school and classroom is connected. Why then, has it not transformed education? Consider these five ways educators can begin to optimize classroom technology and rethink its use. • See technology as a complement rather than a replacement • Embrace its creation potential over consumption function • Encourage design and personalized learning over standards and outcomes • Celebrate the journey toward digital competence over curriculum improvement • Focus on tech-pedagogy over product usage Learn how to let technology cultivate student autonomy, creativity, and responsibility while focusing on lessons that hone higher-order and critical thinking skills. "Dr. Zhao continues to push educators' thinking by taking a serious examination of the role technology has played in education. The struggles he lays out are challenges educators try to overcome on an almost daily bases. The new thinking in this book needs to be read by those in the classroom and leaders alike." Steven W. Anderson, Author Content Curation: How to Avoid Information Overload, @web20classroom This book masterfully address the issues related to technology integration in schools. Dr. Zhao artfully navigates through the misconception of technology as the ultimate solution to the challenges of teaching. Jared Covili, Author of Going Google and Classroom in the Cloud.